Jama'ah Tani Muhammadiyah: A Sharia-Compliant Agricultural Business Model - Alfain Jalaluddin Ramadlan; Dian Berkah (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2026)
Jama’ah Tani Muhammadiyah (JATAM) functions as a companion and protector of farmers with the primary aim of strengthening their independence and bargaining position within the agricultural system. This study analyses the business practices of JATAM through the lens of Islamic economic law. The research focuses on identifying the business model developed by JATAM and assessing the extent to which its operational practices align with Islamic economic principles. A qualitative descriptive approach was employed, using in‑depth interviews, field observations, and analysis of organisational documents and financial records. The findings show that JATAM implements a community‑based agricultural business model that collectively integrates production, capital, and marketing. JATAM acts as a facilitator by providing production inputs, offering farming assistance, and managing the distribution of agricultural products for its member farmers. This model reflects key Islamic economic principles, including the avoidance of usury, the application of profit‑sharing mechanisms, and the strengthening of mutual assistance (ta’awun). Its implementation contributes to improving farmers’ welfare, as evidenced by increased production capacity, fairer access to Sharia‑compliant capital, more equitable marketing systems, and stronger bargaining power for farmers. Despite these positive outcomes, several challenges remain, particularly in ensuring consistent adherence to Sharia principles. These challenges include weaknesses in financial documentation, limited clarity in the formulation of Sharia contracts, and the need for more professional and sustainable institutional development. The study highlights that applying Islamic economic principles within modern agricultural enterprises through community‑based institutional models such as JATAM offers a strategic pathway for strengthening the economic resilience of the ummah and empowering farmers.